Communication Skills Training for Physicians Improves Patient Satisfaction - Boissy, Adrienne; Windover, Amy K.; Bokar, Dan; Karafa, Matthew; Neuendorf, Katie; Frankel, Richard M.; Merlino, James; Rothberg, Michael B. (Journal of general internal medicine : JGIM, 2016)
ABSTRACT BACKGROUND Skilled physician communication is a key component of patient experience. Large-scale studies of exposure to communication skills training and its impact on patient satisfaction have not been conducted. OBJECTIVE We aimed to examine the impact of experiential relationship-centered physician communication skills training on patient satisfaction and physician experience. DESIGN This was an observational study. SETTING The study was conducted at a large, multispecialty academic medical center. PARTICIPANTS Participants included 1537 attending physicians who participated in, and 1951 physicians who did not participate in, communication skills training between 1 August 2013 and 30 April 2014. INTERVENTION An 8-h block of interactive didactics, live or video skill demonstrations, and small group and large group skills practice sessions using a relationship-centered model. MAIN MEASURES Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS), Clinician and Group Consumer Assessment of Healthcare Providers and Systems (CGCAHPS), Jefferson Scale of Empathy (JSE), Maslach Burnout Inventory (MBI), self-efficacy, and post course satisfaction. KEY RESULTS Following the course, adjusted overall CGCAHPS scores for physician communication were higher for intervention physicians than for controls (92.09 vs. 91.09, p < 0.03). No significant interactions were noted between physician specialty or baseline CGCAHPS and improvement following the course. Significant improvement in the post-course HCAHPS Respect domain adjusted mean was seen in intervention versus control groups (91.08 vs. 88.79, p = 0.02) and smaller, non-statistically significant improvements were also seen for adjusted HCAHPS communication scores (83.95 vs. 82.73, p = 0.22). Physicians reported high course satisfaction and showed significant improvement in empathy (116.4 ± 12.7 vs. 124 ± 11.9, p < 0.001) and burnout, including all measures of emotional exhaustion, depersonalization, and personal accomplishment. Less depersonalization and greater personal accomplishment were sustained for at least 3 months. CONCLUSIONS System-wide relationship-centered communication skills training improved patient satisfaction scores, improved physician empathy, self-efficacy, and reduced physician burnout. Further research is necessary to examine longer-term sustainability of such interventions.